2019
DOI: 10.21273/hortsci13634-18
|View full text |Cite
|
Sign up to set email alerts
|

Light and Temperature Independently Influence Methoxypyrazine Content of Vitis vinifera (cv. Cabernet Sauvignon) Berries

Abstract: Methoxypyrazines (MPs) are fruit-derived extractable compounds that contribute to cultivar-specific aroma traits in wine, and greater concentrations can contribute to unpleasant vegetative aromas. Both light exposure and temperature have been reported to influence MP content in developing wine grapes, but individual effects of light and temperature are confounded. A novel method of manipulating light exposure with light-emitting diodes (LEDs) was used to impose light treatments with little or no effect on clus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…Similarly, Šuklje et al (2014) found increased concentration of thiols in clusters exposed to sunlight, and it is generally known that light exposure during ripening reduces MP content in berries (Roujou de Boubee et al, 2000;Sala et al, 2004;Stummer et al, 2005;Darriet et al, 2012;Sidhu et al, 2015;Martin et al, 2016;Cassandra et al, 2019;Torres et al, 2020a). Interestingly, according to Koch et al (2012), higher light intensity before and not during ripening has a greater impact of methoxypyrazine concentration at harvest.…”
Section: Impact Of Radiation On Aroma Compoundsmentioning
confidence: 93%
“…Similarly, Šuklje et al (2014) found increased concentration of thiols in clusters exposed to sunlight, and it is generally known that light exposure during ripening reduces MP content in berries (Roujou de Boubee et al, 2000;Sala et al, 2004;Stummer et al, 2005;Darriet et al, 2012;Sidhu et al, 2015;Martin et al, 2016;Cassandra et al, 2019;Torres et al, 2020a). Interestingly, according to Koch et al (2012), higher light intensity before and not during ripening has a greater impact of methoxypyrazine concentration at harvest.…”
Section: Impact Of Radiation On Aroma Compoundsmentioning
confidence: 93%
“…Vines were bilateral cordon trained (cordons established 0.9 m above the soil), and spur-pruned to four spurs for each cordon, with two buds for each spur. Canopies were managed in a sprawl configuration, with single foliage catch wires at ≈ 15.0 cm, and ≈ 37.0 cm above each cordon (Plank et al 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, there were 36 total vines, and 18 vines for each cultivar and shoot treatment combination. Prior to, and during experiment years, vines were irrigated through a drip irrigation system (Plank et al 2019). In addition, during each growing season, all vines were managed according to viticultural practices common for the Texas High Plains AVA (Kamas 2017, Townsend and Hellman 2014).…”
Section: Methodsmentioning
confidence: 99%
“…The chemical component responsible for bell pepper aroma, 2-methoxy-3-isobutylpyrazine (MIBP), was positively associated by regression to vineyard altitude and lower seasonal temperature ( Falcão et al, 2007 ). Pyrazine’s accumulation is known to be lower with cooler climates ( Romero et al, 2006 ; Plank et al, 2019 ), and their degradation has been linked to sunlight exposure ( Koch et al, 2012 ; Sivilotti et al, 2016 ). Furthermore, after a sensory evaluation of Merlot and Cabernet Sauvignon wines from 2,282, 2,435 and 2,608 m a.s.l., the trained panelists scored higher those wines coming from higher altitudes, highlighting an improvement in characteristics such as taste quality and aroma intensity ( Jin et al, 2017 ).…”
Section: Altitude and Chemical Composition Of Grapes And Winesmentioning
confidence: 99%